Treatment efficiency and economic benefit of Zartech poultry slaughter house waste water treatment plant, Ibadan, Nigeria (2008)
The efficiency of the poultry wastewater treatment plant of Zartech Limited, Ibadan, Nigeria, was assessed based on percentage reduction of the various water contaminants while the unit cost of treated water was compared with that supplied through tankers. Wastewater and treated water samples were respectively collected from the points of generation and release after treatment for laboratory analysis for Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), total suspended solids (TSS), oil and grease, nitrate, phosphate and pH. The values for BOD, COD, TSS, oil and grease, nitrate and phosphate obtained for the wastewater were 1680, 5199, 7125, 1266, 70.0 and 6.8 mg/I, as against 22.8, 15.6, 0, 15.2, 0 and 0 mg/l, respectively, for the treated water. This translates to treatment efficiencies in percentages of 98.7, 99.7, 100.0, 98.8, 100.0 and 100.0 for BOD, COD, TSS, oil and grease, nitrate and phosphate, respectively. The pH of the wastewater was 6.7 as against 7.2 for the treated water. Based on the results obtained, the plant was adjudged efficient for the treatment of poultry wastewater. The cost of treated water was N0.18/l compared with N0.50/1for that supplied through tankers, resulting in a daily savings of about N120,506.95. Further cost reduction can be achieved through adjustment of dozing pumps.